2009
DOI: 10.1016/j.jacc.2008.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Renal Clearance of B-Type Natriuretic Peptide and Amino Terminal Pro-B-Type Natriuretic Peptide

Abstract: Contrary to widespread belief (but in line with the renal physiology of SMWP), BNP and NT-proBNP are equally dependent on renal function for their clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
118
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 49 publications
10
118
1
4
Order By: Relevance
“…Recent reports showed that NT-proBNP and BNP are equally dependent on renal function for clearance, suggesting also a saturable clearance mechanism for NT-proBNP degradation independent of glomerular filtration, yet unknown (10). NTproBNP has a longer half-life (70Á120 min) that may allow for greater accumulation and potentially greater sensitivity in detecting more subtle structural and functional changes (9,10). In our population, NT-proBNP was directly correlated with age, hypertension, diabetes and smoking and inversely correlated with eCrCl and weight, confirming previous studies, particularly on eCrCl and obesity (11,12).…”
Section: Discussionsupporting
confidence: 86%
“…Recent reports showed that NT-proBNP and BNP are equally dependent on renal function for clearance, suggesting also a saturable clearance mechanism for NT-proBNP degradation independent of glomerular filtration, yet unknown (10). NTproBNP has a longer half-life (70Á120 min) that may allow for greater accumulation and potentially greater sensitivity in detecting more subtle structural and functional changes (9,10). In our population, NT-proBNP was directly correlated with age, hypertension, diabetes and smoking and inversely correlated with eCrCl and weight, confirming previous studies, particularly on eCrCl and obesity (11,12).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, NT-BNP-76 is more stable in vitro, and the higher concentration makes it easier to measure than BNP-32 (29). A different effect of renal elimination between BNP-32 and NT-BNP-76 has been described (30) but not confirmed by a study of the dependence of NT-BNP-76 and BNP-32 on renal clearance (31). Further studies of both markers simultaneously are required to better elucidate the factors causing the differential increase in their concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of NT-proBNP and TnT are commonly elevated in patients with reduced kidney function (15)(16)(17)(18)(19)(20)(21), resulting from multiple physiologic stresses, including extracellular volume expansion, LVH, myocardial ischemia, and possibly, reduced renal clearance (16,20,(22)(23)(24). Most studies to date have primarily focused on the association between NT-proBNP and TnT and cardiovascular and/or all-cause death.…”
Section: Introductionmentioning
confidence: 99%